An investigation into the use of anaerobic digestion for the treatment of tannery wastewaters - Jackson-Moss, Clive Alan (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1991)
The anaerobic digestion of tannery wastewaters was investigated with a view to using this form of treatment in the tanning industry. As these wastewaters are extremely complex and contain high concentrations of both inorganic and organic compounds, the effect of these individual compounds on the anaerobic digestion process was investigated in detail, in order to ascertain the fate of these compounds during the digestion process. The experiments comprising the initial toxicity study were carried out as adaptation experiments using a synthetic wastewater. It was found that the heavy metals such as chrome, aluminium and iron precipitated and accumulated in the sludge bed of the digesters . The soluble ions such as sodium and chloride were not retained and passed through the digesters. Approximately 20 % of the calcium ions were removed through precipitation, with the remainder being present in the digester effluent . Under the anaerobic conditions, ammonification of the organic nitrogen occurred, and influent sulphates were reduced to sulphides . These sulphides were present as either H2S, HS or insoluble sulphides. As these compounds under investigation on caused no inhibition of the anaerobic digestion process at the concentrations found in tannery wastewaters, the anaerobic treatment of these wastewaters appeared to be possible, provided the bacteria were given sufficient time to adapt to the potentially toxic compounds. However, despite the findings of the synthetic study, the successful anaerobic digestion of the tannery effluents could not be achieved. Although the use of acid was found to be essential in order to control the digester pH in the optimum range, the metabolism of the methanogenic bacteria was inhibited by the presence or absence of unknown compounds. Neither the addition of essential trace nutrients, nor the prevention of the competition between the methanogens and the sulphate-reducing bacteria were able to reverse this inhibition. As tannery effluents contain very low concentrations of phosphorous, it is possible that the methanogens were inhibited by a lack of phosphorous, which is essential during methanogenesis. In contrast to the results obtained from the effluent experiments, the anaerobic digestion of tannery sludge was found to be possible. Of the organic solids present in the sludge, 60 % were degraded and converted into biogas, which had a methane content greater than 70 %. The degradation of the organic solids ensured that COD and PV reductions of greater than 90 % were achieved, and the fate of the compounds in the digesters were in agreement with the findings of the v synthetic study. Efforts to improve the efficiency of the digestion process through the addition of trace nutrients and the use of a two-stage process were only successful in bringing about a minor improvement in digester performance. The overall results of this investigation show, therefore, that although the anaerobic treatment of the tannery effluent was not achieved, the successful anaerobic digestion of tannery sludge is possible at low loading rates. As many difficulties still need to be solved, a great deal of further research is necessary if anaerobic digestion is to be used on an industrial scale for the treatment and disposal of tannery wastewaters.
Keywords: Tanneries -- Waste disposal; Sewage sludge -- South Africa -- Management; Sewage -- Purification -- Biological treatment -- South Africa; Water quality management -- South Africa; Water -- Purification -- Biological treatment -- South Africa